Digital Economy for Zimbabwe : Country Diagnostic Report - World Bank (World Bank, Washington, DC, 2021)
A diagnostic assessment of Zimbabwe's digital economy has been launched as part of the World Bank Group's Digital Economy for Africa (DE4A) Initiative, which leverages an integrated and foundations- based diagnostic framework to examine the present level of digital economy development across Africa. The assessment maps the current strengths and weaknesses that characterize the national digital economy ecosystem in Zimbabwe as well as identifies the challenges and opportunities for future growth.